Studies in Byzantine Epitomes and the Greek Epitomizing Tradition - Mallan, C.T., (Classical Studies E-Books Online, Collection 2025, 2025)
Epitomes, or abridged books, were a constant feature of Byzantine intellectual life and book culture. From epitomes of Greek and Roman historians to medical texts to condensed works of law, epitomes provided professionals and intellectuals with convenient sources of information - or erudition - that met the needs of their post-antique world. This volume, the first to be devoted to Byzantine epitomes, traces the development of the Byzantine epitomizing tradition from antiquity to the fall of Constantinople, while also analysing several key examples in depth. Across eight case-studies, Byzantine epitomes emerge as often surprising products of times of intense intellectual activity.